To factor the perfect square trinomials, we can use the formulas:
\[ (a + b)^2 = a^2 + 2ab + b^2 \] \[ (a - b)^2 = a^2 - 2ab + b^2 \]
Now we will factor each trinomial:
-
\(x^2 + 6x + 9\)
We recognize this as the expansion of \((x + 3)^2\).\[ x^2 + 6x + 9 = (x + 3)^2 \]
-
\(x^2 + 10x + 25\)
This is the expansion of \((x + 5)^2\).\[ x^2 + 10x + 25 = (x + 5)^2 \]
-
\(9x^2 + 12x + 4\)
This can be factored as \((3x + 2)^2\).\[ 9x^2 + 12x + 4 = (3x + 2)^2 \]
-
\(9x^2 - 30x + 25\)
This can be factored as \((3x - 5)^2\).\[ 9x^2 - 30x + 25 = (3x - 5)^2 \]
Putting it all together, the factored forms of the given perfect square trinomials are:
- \( (x + 3)^2 \)
- \( (x + 5)^2 \)
- \( (3x + 2)^2 \)
- \( (3x - 5)^2 \)